Heat‐shock protein 70 binds microtubules and interacts with kinesin in tobacco pollen tubes. Issue 9 (8th October 2013) - Parrotta, Luigi; Cresti, Mauro; Cai, Giampiero
<x xml:space="preserve">Abstract</x> The heat‐shock proteins of 70 kDa are a family of ubiquitously expressed proteins important for protein folding. Heat‐shock protein 70 assists other nascent proteins to achieve the spatial structure and ultimately helps the cell to protect against stress factors, such as heat. These proteins are localized in different cellular compartments and are associated with the cytoskeleton. We identified a heat‐shock protein 70 isoform in the pollen tube of tobacco that binds to microtubules in an ATP‐dependent manner. The heat‐shock protein 70 was identified as part of the so‐called ATP‐MAP (ATP‐dependent microtubule‐associated protein) fraction, which also includes the 90‐kDa kinesin, a mitochondria‐associated motor protein. The identity of heat‐shock protein 70 was validated by immunological assays and mass spectrometry. Sequence analysis showed that this heat‐shock protein 70 is more similar to specific heat‐shock proteins of Arabidopsis than to corresponding proteins of tobacco. Two‐dimensional electrophoresis indicated that this heat‐shock protein 70 isoform only is part of the ATP‐MAP fraction and that is associated with the mitochondria of pollen tubes. Sedimentation assays showed that the binding of heat‐shock protein 70 to microtubules is not affected by AMPPNP but it increases in the presence of the 90‐kDa kinesin. Binding of heat‐shock protein 70 to microtubules occurs only partially in the presence of ATP but it does not occur if, in addition to ATP, the 90‐kDa kinesin is also present. Data suggest that the binding (but not the release) of heat‐shock protein 70 to microtubules is facilitated by the 90‐kDa kinesin. © 2013 Wiley Periodicals, Inc.